Exercise in deriving meaning from context for the building and developing of vocabulary - Honculada, Juanita Alviola 1926- (1969)
This seminar paper explored the feasibility of helping the Filipino high school students deduce the meaning of certain words through their use in a phrase, a sentence or a paragraph. Exercises were based on portions chosen from selections taken from the Reader's Digest Reading Skill and Power Builders.In conclusion, as seen from this paper, the meaning of a word, a phrase, sentence and a quotation can be drawn from context.